Mid-arm muscle circumference cutoff points in patients with cirrhosis: Low muscle mass related to malnutrition predicts mortality - Saueressig, Camila; Alves, Bruna Cherubini; Luft, Vivian Cristine; Anastácio, Lucilene Rezende; Santos, Bárbara Chaves; Ferreira, Lívia Garcia; Fonseca, Ana Luísa Ferreira; Jesus, Rosângela Passos de; Oliveira, Lucivalda Pereira Magalhães de; Boulhosa, Ramona Souza da Silva Baqueiro; Lyra, André Castro; Romeiro, Fernando Gomes [UNESP]; et al. (Elsevier, 2024)
Objectives: Muscle loss is one of the phenotypic criteria of malnutrition, is highly prevalent in patients with cirrhosis, and is associated with adverse outcomes. Mid-arm muscle circumference (MAMC) estimates the skeletal muscle mass and is especially helpful in cases of fluid overload. This study aimed to propose MAMC cutoff points for patients with cirrhosis and demonstrate its association with 1-year mortality. Methods: This is an analysis of cohort databases from five reference centers in Brazil that included inpatients and outpatients with cirrhosis aged ≥18 y. The nutritional variables obtained were the MAMC (n = 1075) and the subjective global assessment (n = 629). We established the MAMC cutoff points stratified by sex based on the subjective global assessment as a reference standard for malnutrition diagnosis, considering the sensitivity, specificity, and Youden index. An adjusted Cox regression model was used to test the association of MAMC cutoff points and 1-year mortality. Results: We included 1075 patients with cirrhosis, with a mean age of 54.8 ± 11.3 y; 70.4% (n = 757) male. Most patients had alcoholic cirrhosis (47.1%, n = 506) and were classified as Child-Pugh B (44.7%, n = 480). The MAMC cutoff points for moderate and severe depletion were ≤21.5 cm and ≤24.2 cm; ≤20.9 cm and ≤22.9 cm for women and men, respectively. According to these cutoff points, 13.8% (n = 148) and 35.1% (n = 377) of the patients had moderate or severe MAMC depletion, respectively. The 1-year mortality rate was 17.3% (n = 186). In the multivariate analysis adjusted for sex, age, MELD-Na, and Child-Pugh scores, a severe depletion in MAMC was an independent increased risk factor for 1-year mortality (HR: 1.71, 95% CI: 1.24–2.35, P < 0.001). Each increase of 1 cm in MAMC values was associated with an 11% reduction in 1-year mortality risk (HR: 0.89, 95% CI: 0.85–0.94, P < 0.001). Conclusions: Low MAMC classified according to the new cutoff points predicts mortality risk in patients with cirrhosis and could be used in clinical practice.
Keywords: Anthropometric measurements; Liver cirrhosis; Low muscle mass; Nutritional assessment